Erratum on "two-way ANOVA when the distribution of the error terms is skew t" [Nuri Celik & Birdal Senoglu, Communications in statistics - simulation and computation, volume 48, issue 1 (2019), pages: 287-301, DOI: 10.1080/03610918.2017.1377242] - Kharrati-Kopaei, Mahmood (Communications in statistics. Simulation and computation, 2024)
Celik and Senoglu (Communications in Statistics-Simulation and Computation 48 (1):287-301, 2019) proposed a two-way analysis of variance (ANOVA) model when the distribution of the error terms is skew t . They obtained the estimators of the model parameters by using the maximum likelihood (ML) and the modified maximum likelihood (MML) methodologies. They also proposed test statistics based on these estimators for testing the main hypotheses in a two-way ANOVA model. They finally compared the efficiencies of the ML and the MML estimators and the power of the test statistics with the corresponding normal theory results via a Monte Carlo simulation study. Unfortunately, they wrongly presented one of the maximum likelihood equations and consequently, some parts of the simulation results and conclusions are questionable.